Reporte de caso de Peritonitis Infecciosa Felina (PIF) en un paciente de clínica veterinaria en el Sur de Bogotá (2025)
The Zoolandia San Rafael veterinary clinic is located south of the city of Bogotá, in the town of Puente Aranda, the clinic has two floors, which offers general medical consultation and assessment services, basic and specialist surgeries, it has with imaging and laboratory services; During the internship I had the opportunity to be present in different clinical cases and support the medication assessment and supervision of them, among which I was able to see: Manolito, a male cat, 13 year old, was taken to the Zoolandia San Rafael veterinary clinic due to a change in his health, shortly after a cat he lived with fell ill with symptoms associated with Feline Infectious Peritonitis (FIP) and died